Description of two new species of Neoplea Esaki & China (Hemiptera: Pleidae) from Colombia - Cook, Jerry L.; Mondragón-F., Silvia P.; Morales, Irina (Zootaxa, 2020)
Neoplea hyaloderma n. sp. and N. melanosoma n. sp. (Insecta: Hemiptera: Pleidae) are described from Colombia. This increases the number of species of pleids known from Colombia to four, all of which are in the genus Neoplea Esaki & China. A key to the species of Neoplea of Colombia is included. Neoplea melanosoma appears to be part of a species complex with N. maculosa (Berg) and N. tenuistyla Roback & Nieser, and herein is called the N. maculosa species complex. We also note that there is probably at least one additional species in this complex from Suriname that was previously identified as N. maculosa. Neoplea melanosoma n. sp. appears to most closely resemble N. maculosa from Argentina, Bolivia and Paraguay than the geographically closer N. tenuistyla. Neoplea hyaloderma n. sp. appears most closely related to N. lingula Roback & Nieser, which is also in Colombia.